(y - 1)(3y + 7)
(4x + 7y)(16x2 - 28xy + 49y2)
15x - 3xy = 3x(5 - y) 20 - 4y = 4(5 - y) 15x - 3xy + 20 - 4y = (3x + 4)(5 - y)
The GCF of 4y and 12 is 3.
Factor out a 2; so it is 2(x+2y).
2x2 + 28xy + 98y2 = 2(x + 7)2.
If you mean 7 times 4y then it is 28y If you mean 7x times 4y then it is 28xy
4x^(2) + 28xy + 49y^(2) -> (2x)^(2) + 28xy + (7y)^2 Split into brackets ( 2x + 7y)(2x + 7y) If you applyuFOIL you will find toy come to '28xy'. The clue to this problem is to note that '4' ^ '49' are both squared numbers.
x2 -y2 +4y-4=(x+y)(x-y)+4y-4
All you can do to factor that expression is to divide both terms by y: y2 + 4y = y(y + 4)
(4y + 1)(y + 6)
Factor out the 4. The answer is y-3/y+3
(x + 3)(x + 4y)
4y - 3
The GCF is 4.
7(5x + 4y)
(4y + 1)(3y + 2)